Adoption and impact of technology in the rice-wheat system - ANBUKKANI, P; SHALOO, SHALOO; PAL, SURESH (The Indian Journal of Agricultural Sciences, 2020)
In this study the adoption, impact of varieties and resource management practices in selected states of India, viz. Punjab, Haryana and Uttar Pradesh has been examined during 2014-15. The economic surplus method was used to calculate impact of variety and technology. Result revealed that rate of varietal improvement and notification has increased for both rice and wheat, but there is varietal concentration. Top three varieties contributed more than threefourths of total seed sale in the region. The estimated IRR was 38.8% and the ratio of net benefits to the cost was 17.31 which are slightly lower than the rates reported in the past. Nevertheless, these returns are quite high to justify higher allocation of public funds to agricultural research.